Temporal effects of maternal and pregnancy characteristics on serum pregnancy‐associated plasma protein‐A and free β‐human chorionic gonadotropin at 7–14 weeks' gestation. (4th December 2012) - Ball, S.; Ekelund, C.; Wright, D.; Kirkegaard, I.; Nørgaard, P.; Petersen, O. B.; Tabor, A.; ,
Abstract: Objective: The aim of this study was to investigate gestational age‐dependent effects of racial origin, smoking status and mode of conception on maternal serum levels of free β‐human chorionic gonadotropin (β‐hCG) and pregnancy‐associated plasma protein‐A (PAPP‐A) at 7–14 weeks' gestation . Methods: This was an analysis of data from prospective first‐trimester combined screening for aneuploidies in singleton pregnancies, with β‐hCG and PAPP‐A measured at 7 + 1 to 14 + 3 weeks' gestation. We included 27 908 pregnancies from three centers in the UK and 125 461 pregnancies from 22 centers in Denmark, all with known normal fetal karyotype or resulting in the birth of a phenotypically normal neonate. Multiple regression modelling of log10 ‐transformed marker concentrations was used to produce log10 multiple of the median (MoM) values for free β‐hCG and PAPP‐A and to examine pregnancy characteristics that have significant effects on marker concentrations . Results: Serum free β‐hCG and PAPP‐A concentrations were significantly affected by gestational age, maternal weight, racial origin, parity, smoking and mode of conception. There were significant gestational age‐dependent effects attributed to Afro‐Caribbean race, smoking and conception through in‐vitro fertilization (IVF) on PAPP‐A and free β‐hCG levels. In women of Afro‐Caribbean race there was a weekly increase in PAPP‐A of 5.3% and in free β‐hCG of 1.8%. In smokers there was a weekly decrease in PAPP‐A of 2.4% and in free β‐hCG of 1.6%. In cases of IVF conceptions there was a weekly increase in PAPP‐A of 4.5% and in free β‐hCG of 4.6% . Conclusions: Serum free β‐hCG and PAPP‐A concentrations at 7–14 weeks' gestation are affected by several pregnancy characteristics. The effects of Afro‐Caribbean race, smoking and IVF conception change with gestational age .